Acetylation of Hsp90 reverses dexamethasone-mediated inhibition of insulin secretion. (1st March 2020) - Zhu, Kecheng; Zhang, Yumei; Zhang, Juan; Zhou, Feiye; Zhang, Linlin; Wang, Shushu; Zhu, Qin; Liu, Qianqian; Wang, Xiao; Zhou, Libin
Highlights: Dexamethasone decreased glucose-stimulated insulin secretion and increased NYP and SSTR3 expressions in rat islets. Hsp90 inhibition reversed the regulations of dexamethasone on insulin secretion as well as NYP and SSTR3 expressions. Two HDAC inhibitors TSA and Tubacin counteracted dexamethasone-impaired islet function. The acetylation of Hsp90 decreased its binding to GR and promoted GR protein degradation. The acetylation of Hsp90 by inhibiting HDAC6 activity blocked dexamethasone-elicited GR nuclear import and transactivation. Abstract: The deleterious effects of glucocorticoids on glucose homeostasis limit their clinical use. There is substantial evidence demonstrating that islet function impaired by long-term glucocorticoids exposure is a core defect in the progression of impaired glucose tolerance to diabetes. The activity of heat-shock protein (Hsp) 90 is required to maintain the hormone-binding activity and stability of glucocorticoid receptor (GR). In the present study, Hsp90 inhibition by 17-DMAG counteracted dexamethasone-mediated inhibition of glucose-stimulated insulin secretion in isolated rat islets as well as expressions of neuropeptide Y (NPY) and somatostatin receptor 3 (SSTR3), two negative regulators of insulin secretion. Like 17-DMAG, both the pan-histone deacetylase (HDAC) inhibitor TSA and HDAC6 inhibitor Tubacin exhibited a similar action in protecting islet function against dexamethasone-induced injury, along with the downregulation of NPY and SSTR3 expressions. The hyperacetylation of Hsp90 by TSA and Tubacin disrupted its binding ability to GR and blocked dexamethasone-elicited nuclear translocation of GR in INS-1 β-cell lines. In addition, Tubacin treatment triggered the GR protein degradation through the ubiquitin-proteasome pathway. These findings suggest that Hsp90 acetylation by inhibiting HDAC6 activity may be a potential strategy to prevent the development of steroid diabetes mellitus via alleviating glucocorticoid-impaired islet function.